Detection of extended-spectrum β-Lactamase-producing Klebsiella pneumoniae isolated from four provincial hospitals in Luzon and genotyping of β-Lactamase (blaCTX-M, blaTEM, blaSHV, and blaOXA-1) genes - Cornista, Joel C. (Philippine Journal of Science, 2019)
Extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae is one of the most common cause of nosocomial infections. One hundred isolates of K. pneumoniae were obtained from four different provincial hospitals in Luzon. The strains following purification and standard bacteriological testing were then initially screened for antimicrobial susceptibility against five 3rd generation cephalosporins and monobactam. Twenty-three isolates (23%) were initially found to be resistant to all or at least three antibiotics tested. To prove ESBL-production, the phenotypic confirmatory disk diffusion test (PCDDT) was conducted confirming 18 out of the 23 (78.3%) isolates to be ESBL producers. The identity of the isolates was confirmed as K. pneumoniae by the amplification and sequencing of the 16S rRNA gene through polymerase chain reaction (PCR). To determine the type of the β-lactamase genes carried by the ESBL-producing K. pneumoniae isolates, the blaCTXM, blaOXA-1, blaSHV, and blaTEM were amplified and sequenced. This study showed that blaCTX-M and blaTEM were detected in 10 out of 18 ESBL-positive isolates (56%), while blaSHV was found in 15 out of 18 isolates (83.3%). Interestingly, the blaOXA-1 gene was detected in all phenotypically confirmed ESBL isolates suggesting that it was the most predominant β-lactamase gene among the samples. Eight of the isolates harbored at least three genes; four of these isolates have blaCTX-M, blaOXA-1, and blaSHV; three of the isolates have blaTEM, blaOXA-1, and blaSHV; and one with blaCTX-M, blaOXA-1, and blaTEM. Lastly, five isolates harbored all the four genes tested – suggesting that these isolates pose a serious threat in the healthcare industry because of its resistance to a wider range of antibiotics. Because of the occurrence of multiple β-lactamase genes in K. pneumoniae , there is therefore an urgent need to develop a rapid and accurate method of ESBL genotyping.